Acute presentation of undiagnosed vaginal leiomyoma in pregnancy - Mishra, Vidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Vaginal leiomyomas are rare benign solid tumors of the vagina. There are approximately 300 case reports available in the literature and the para-urethral site is extremely uncommon. Here we report a case of 29 a year old primi-gravida who presented with complaints of sudden protrusion of mass arising from anterior vaginal wall at 16 weeks of pregnancy. On per-vaginum examination firm, mildly tender mass 6×4×5 cm was palpated arising from the lower one third of anterior vaginal wall and ending approximately 1 cm proximal to the external urethral meatus, occupying whole of the introitus and it was separate from the cervix. Trans-vaginal surgical enucleation of the vaginal leiomyoma was done. Post-operative histopathology confirmed as leiomyoma.